Nomadic primary education: bridging the challenges facing educational development in Nigeria (2018)
The World Education Forum in Dakar, Senegal in 2000, countries across the world declared that “no countries seriously committed to Education for All (EFA) will be frustrated in their achievement of this goal by lack of resources”. Yet, only 0.2% of the over 9.3 million nomads in Nigeria are literate who are just a part of other social groups that are termed educationally disadvantaged thereby deepening the challenges facing the educational sector in Nigeria cum Africa due to their non-sedentary nature. Consequently, the nomadic primary education programme was established to bridge the challenges facing the sector by providing quality education service to the nomads. This study, using 5 research questions sought to End out the perception of the respondents on the challenges facing the effective implementation of the nomadic primary education programme. The instrument used to collect data was the questionnaire which was administered to 400 respondents selected from twenty different nomadic primary schools in Kaduna State, Nigeria. The design was a survey. Data collected were analyzed using both descriptive and inferential method of statistics. The study showed that there is dearth of teachers in the nomadic primary schools; instructional facilities are grossly inadequate, lack of adequate grazing reserves, inadequate funding and the problem of constant migration among others. Summary and conclusion were